Hypothesis: The Psychedelic Ayahuasca Heals Traumatic Memories via a Sigma 1 Receptor-Mediated Epigenetic-Mnemonic Process - Inserra, Antonio (Frontiers in Pharmacology, 2018)
Ayahuasca ingestion modulates brain activity, neurotransmission, gene expression and epigenetic regulation. N,N-Dimethyltryptamine (DMT, one of the alkaloids in Ayahuasca) activates sigma 1 receptor (SIGMAR1) and others. SIGMAR1 is a multi-faceted stress-responsive receptor which promotes cell survival, neuroprotection, neuroplasticity and neuroimmunomodulation. Simultaneously, monoamine oxidase inhibitors (MAOIs) also present in Ayahuasca prevent the degradation of DMT. One peculiarity of SIGMAR1 activation and MAOI activity is the reversal of mnemonic deficits in pre-clinical models. Since traumatic memories in post-traumatic stress disorder (PTSD) are often characterised by “repression” and PTSD patients ingesting Ayahuasca report the retrieval of such memories, it cannot be excluded that DMT-mediated SIGMAR1 activation and the concomitant MAOIs effects during Ayahuasca ingestion might mediate such “anti-amnesic” process. Here I hypothesise that Ayahuasca, via hyperactivation of trauma and emotional memory-related centres, and via its concomitant SIGMAR1- and MAOIs- induced anti-amnesic effects, facilitates the retrieval of traumatic memories, in turn making them labile (destabilised). As Ayahuasca alkaloids enhance synaptic plasticity, increase neurogenesis and boost dopaminergic neurotransmission, and those processes are involved in memory reconsolidation and fear extinction, the fear response triggered by the memory can be reprogramed and/or extinguished. Subsequently, the memory is stored with this updated significance. To date, it is unclear if new memories replace, co-exist with or bypass old ones. Although the mechanisms involved in memory are still debated, they seem to require the involvement of cellular and molecular events, such as reorganization of homo and heteroreceptor complexes at the synapse, synaptic plasticity, and epigenetic re-modulation of gene expression. Since SIGMAR1 mobilizes synaptic receptor, boosts synaptic plasticity and modulates epigenetic processes, such effects might be involved in the reported healing of traumatic memories in PTSD patients. If this theory proves to be true, Ayahuasca could come to represent the only standing pharmacological treatment which targets traumatic memories in PTSD. Lastly, since SIGMAR1 activation triggers both epigenetic and immunomodulatory programs, the mechanism here presented could help understanding and treating other conditions in which the cellular memory is dysregulated, such as cancer, diabetes, autoimmune and neurodegenerative pathologies and substance addiction.